Comparison of oxidation procedures for removing neonicotinoid insecticides from model solutions - Truzsi, Alexandra; Szmolka, Mónika; Bodnár, Ildikó; Varga, József (International Journal of Engineering and Management Sciences, 2019)
The main objective of this study is to remove three neonicotinoid insecticide agents (thiametoxam, acetamiprid, thiakloprid) from model solutions using ferrate and persulfate-based oxidation techniques. In our experiments, an analytical method was developed for HPLC-MS/MS coupled techniques and tests were performed to determine how the molar ratio of the starting target compound/oxidant affects the degree of removal of the target components.